The geometry of space and gesture in scene: a reading of Os arqueólogos (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This essay focuses on the analysis of the dramaturgical text Os arqueólogos, by Vinicius Calderoni, a writer from São Paulo, offering a reflection on the notion of space and gesture from the evaluation of dramatic textual construction procedures and their philosophical developments. The specificities of the landscape of contemporary dramaturgy, the fragmentation of the fable, and the mythos are considered in the design of episodic writing and its relationship with the photographic chronicle of the present times.
Keywords: Dramaturgy; Space; Gesture; Theory; Catastrophe